Global Liquidity : Availability of Funds for Safe and Risky Assets - Matsumoto, Akito (IMF Working Papers; Working Paper ;, 2011)
What is global liquidity and how does it affect an economy? The paper addresses that question by looking at liquidity from two different perspectives: global liquidity as availability of funds in safe and risky asset markets. This distinction between safe and risky asset markets is important due to market segmentation, which called for unconventional monetary policy to restore a function of risky asset markets. To analyze the effect of global liquidity, I construct proxy variables and then asses how they affect an emerging economy whose interest rate is affected by a world risk-free rate and a risk premium. Using the data from four major Latin American countries, I find that these two aspects of global liquidity have similar effects on economic performance in emerging market economies except for their effect on inflation.